New Research in Children with Neurodevelopmental Disorders - Romero-Ayuso, Dulce María (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book collects recent research in the field of care for neurodevelopmental disorders, emphasizing transdisciplinary work in clinical, educational and family contexts. It presents an opportunity to learn about the impact of participation on children and adolescents with neurodevelopmental disorders. Mainly, new therapeutic approaches are presented in children and adolescents with autism spectrum disorder, attention-deficit/hyperactivity disorder, or motor coordination disorders.